2018
DOI: 10.21037/tau.2017.12.24
|View full text |Cite
|
Sign up to set email alerts
|

Active surveillance for prostate cancer: a systematic review of contemporary worldwide practices

Abstract: In the last decade, active surveillance (AS) has emerged as an acceptable choice for low-risk prostate cancer (PC), however there is discordance amongst large AS cohort studies with respect to entry and monitoring protocols. We systematically reviewed worldwide AS practices in studies reporting ≥5 years follow-up. We searched PubMed and Medline 2000-now and identified 13 AS cohorts. Three key areas were identified: (I) patient selection; (II) monitoring protocols; (III) triggers for intervention—(I) all studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
122
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(125 citation statements)
references
References 47 publications
(136 reference statements)
2
122
0
1
Order By: Relevance
“…Many of these issues have also been identified in previous systematic reviews of unmet needs in PCa26,27 patients who have undergone treatment.Understanding men's unmet needs during AS may assist researchers and health professionals in empowering men to adhere until treatment is medically necessary. With approximately 10% to 20% of men who begin AS discontinuing without disease progression[18][19][20] , interventions that consider men's experiences and unmet needs are required.…”
mentioning
confidence: 99%
“…Many of these issues have also been identified in previous systematic reviews of unmet needs in PCa26,27 patients who have undergone treatment.Understanding men's unmet needs during AS may assist researchers and health professionals in empowering men to adhere until treatment is medically necessary. With approximately 10% to 20% of men who begin AS discontinuing without disease progression[18][19][20] , interventions that consider men's experiences and unmet needs are required.…”
mentioning
confidence: 99%
“…Data from the University of Toronto prospective AS cohort, which includes some men with intermediate‐risk features, show excellent results, but found that the 15‐year prostate cancer metastasis rate was 3.7 times higher with intermediate‐risk men at baseline, suggesting that such men need to be selected and followed carefully . Results from multiple AS studies with inclusion criteria established prior to the widespread availability of mpMRI or tissue based biomarkers, demonstrate excellent results: this must be appreciated when considering adding any new technology with additional cost to patient care . There is room for improvement, however, especially given relatively high attrition and treatment rates over time .…”
Section: Resultsmentioning
confidence: 99%
“…Results from multiple AS studies with inclusion criteria established prior to the widespread availability of mpMRI or tissue based biomarkers, demonstrate excellent results: this must be appreciated when considering adding any new technology with additional cost to patient care [21]. There is room for improvement, however, especially given relatively high attrition and treatment rates over time [22].…”
Section: Multiparametric Mri and Patient Selectionmentioning
confidence: 98%
“…Of course, this is only permissible in tumours with a very low risk of progression, according to conventional parameters. Most AS regimens include patients with low PSA levels (<10 ng/ml), Gleason score 6 and limited tumour extent on biopsy (one to two cores) . Therefore, biomarkers that broaden these inclusion criteria are highly sought‐after.…”
Section: General Considerations: Biomarker Research and Cohort Implicmentioning
confidence: 99%
“…Most AS regimens include patients with low PSA levels (<10 ng/ml), Gleason score 6 and limited tumour extent on biopsy (one to two cores). 16,17 Therefore, biomarkers that broaden these inclusion criteria are highly soughtafter. Currently, it is unclear if tissue-based molecular testing or novel radiological techniques such as multiparametric MRI will be taking the lead in guiding therapy.…”
Section: General Considerations: Biomarker Research and Cohort Implicmentioning
confidence: 99%